Analisis Pengaruh Karakteristik Individu dan Lingkungan Kerja Terhadap Tingkat Kepuasan Masyarakat Pada Kantor Kecamatan Tambun Selatan (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2023)
Individual characteristics and a good work environment are important factors in providing public services. Because if the service provided is not good, it will affect the level of community satisfaction. This research was conducted at the South Tambun sub-district office located on Jl. Sultan Hasanuddin No. 251, South Tambun, Bekasi Regency, West Java, with the aim of knowing the effect of individual characteristics on the level of community satisfaction, the influence of the work environment on the level of community satisfaction, and the influence of both on the level of community satisfaction in the South Tambun sub-district office. In this research, the authors conducted library and field research (observations, interviews, and questionnaires) using quantitative analysis methods and descriptive analysis using the SPSS version 26 application which included regression coefficient of determination analysis, t-test, and f-test. The results of the analysis using the multiple regression formula obtained a value of Y = -5,317 + 0,392 X1 + 0,776 X2. Thus, the coefficient of determination obtained is 0,657, which means that there is a positive relationship between individual characteristics and the work environment on community satisfaction. The results of the f-test are 0,000<0,05 and the calculated F value is 45.056>F table 3,18 so it can be concluded that H0 is rejected and H3 is accepted, which means that there is an influence of X, and X simultaneously on Y so that it can be seen that individual characteristics and the work environment have significant influence on community satisfaction.